Wide‐bandwidth and tunable PIFAs under dual‐resonance modes. Issue 11 (12th August 2022) - Feng, Yinhai; Yang, Shuo; Zhang, Guanmao; Lun, Yupeng; Li, Zhihang; Yue, Juan; Suo, Junhong; Che, Zonge; Liu, Jie; Du, Shaokai
Abstract: This communication proposes a wide‐bandwidth planar inverted‐F antenna (WPIFA) and a tunable planar inverted‐F antenna (TPIFA), which are realized by manipulating two resonant modes of T M 0, 1 / 2 and T M 0, 3 / 2 . For WPIFA, the dual resonance modes T M 0, 1 / 2 and T M 0, 3 / 2 are made close to each other by appropriately using a pair of shorting pins and etching a Ω ‐shaped slot on the surface of the patch to increase the bandwidth. To realize the tunable bandwidth, on the basis of WPIFA, the Ω ‐shaped slot is modified to close the protruding part, and three PINs are used to control the on–off between the closed part and the outside. It is formed that when the PIN is turn off and on, respectively, TPIFA works in the T M 0, 1 / 2 mode, and works in both the T M 0, 1 / 2 and T M 0, 3 / 2 modes. So that the working bandwidth of TPIFA is switched between narrowband and wideband. The prototype processing and testing of the antennas show that it has excellent performance under low profile ( 0.033 λ 0 ). Among them, the impedance bandwidth of WPIFA is 3.3–3.77 GHz (13.3%), while TPIFA is 3.27–3.56 GHz (8.5%) and 3.26–3.75 GHz (14%) respectively, when the PIN is off and on.